تطبيقات قانونية للوصية الواجبة في المحكمة الشرعية بولاية سلانجور : Legal Applications of the Obligatory Will in the Shariah Court of Selangor - Karim, Fatimah (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
هدفت هذه الدراسة إلى توضيح الخلفية التاريخية للوصية الواجبة في ماليزيا، وتحليل المواد القانونية المتعلقة بالوصية الواجبة تحت البند السابع والعشرين (27) قانون الوصايا للمسلمين بولاية سلانجور 1999م، مع بيان تطبيقاتها القانونية في المحكمة الشرعية بولاية سلانجور لمعرفة مدى وملاءمتها وتوافقها مع الشريعة الإسلامية. لذلك، من أجل دراسة الموضوع تعتمد الباحثة على المنهج الوصفي والمنهج التحليلي. ومن النتائج المهمة التي أسفر عنها البحث بأنه إذا استخدم القاضي طريقة المناسخات لاستخراج مقدار الوصية الواجبة في المحكمة الشرعية بولاية سلانجور، يهتم القاضي بأن مقدارها لا بد أن يكون أقل مقدار حصة أبيهم من الميراث إذا كان حيًا، على ألا يتجاوز هذا المقدار ثلث التركة. ولكن إذا كان أقل من الثلث لا يكمل القاضي مقدار الوصية الواجبة لهؤلاء الأحفاد في حدود الثلث التركة. وعليه، وتقترح هذه الدراسة بأنه إذا كان أعطاهم أقل من الثلث، وجبت تكملته إلى حدود ثلث التركة تحت هذا القانون. This study aims to clarify the historical background of the Obligatory Will in Malaysia, and to analyze the legal articles related to the Obligatory Will under section 27 Muslim Wills Selangor Enactment 1999, with a statement of its legal applications in the Shariah Court of Selangor to determine the extent, suitability, and compatibility with Islamic jurisprudence. Therefore, in order to study the topic, the researcher relies on the descriptive method and the analytical method. One of the important findings of the research is that if the judge uses the Munasakhat method to extract the amount of the Obligatory Will in the Shariah court of Selangor, the judge consideration is that the amount must be less than their father’s share of the inheritance if he is alive, provided that this amount does not exceed one third of the estate. But if it less than one third, the judge will not grant the amount of the Obligatory Will to those grandchildren to the limits of one third of the estate. Thus, this study suggests that if the judge’s verdict is to grant the grandchildren less than one third of the estate, it must be supplemented to the limits of one third of the estate under this law.